Teaching practice for subject of graphic expression through project based learning - Marín-Granados, Manuel Damián; Blázquez-Parra, Elidia Beatriz; Gutiérrez, Francisco Javier; Ladrón-de-Guevara-Muñoz, María del Carmen; Ladrón de Guevara, María Luisa (My University, 2013)
Project-based learning PBL (Aprendizaje Basado en Proyectos, ABP) is a participatory methodology which foments skills demanded by the company, in addition to being a teaching strategy which helps to achieve competence in the subjects of graphic expression at/in the different degrees of industrial engineering. This article presents the design, development, analysis and evaluation of results obtained in a project of computer-aided design, based on PBL, aimed to students in electrical engineering degree from Polytechnic School of Malaga during the biennium 2008/2010, developed in the educational innovation project, PIE08-056.
Comunicación presentada en el XXIII International Conference on Graphic Engineering- Madrid 2013.
Keywords: Enseñanza superior - Métodos activos; Ingeniería - Enseñanza asistida por ordenador; PBL; CAD; COOPERATION